(untitled) (Research, Society and Development, 2022)
The improvement of horizontal drilling techniques and hydraulic fracturing makes shale gas exploration an option economically. Shale gas has the potential to reshape energy policy at national and international levels. Shale gas development can be an effective path to a low-carbon energy transition because natural gas, conventional or unconventional, has relatively lower emissions than other fossil fuels, as well as lower cost and abundant global reserves. This paper uses the SWOT analysis method to identify possibilities and challenges that shale gas development may face. To prepare the analysis, an advanced search was carried out on the Science Direct platform, investigating the strengths (S), weaknesses (W), opportunities (O), and threats (T) of the development of shale gas linked to the energy transition context. The most cited strength was abundant availability, followed by increased energy security. Regarding weaknesses, the most evident were environmental impacts and pollution. The most-reported opportunity for shale gas development was the prospect of replacing other sources, and the threat was public skepticism and less support than there is for renewables, although the ban was also included. A possible path for the development of shale gas, in an energy transition context, is an opportunity to replace other sources, such as coal, taking advantage of its abundance and energy security. However, for development to become relatively clean, fugitive emissions and other negative aspects of exploration must be mitigated.